Understanding the relationship between adolescents with tuberculosis and health services: an indepth qualitative study from Cape Town - Graeme Hoddinott; James Seddon; Khanyisa Mcimeli; Stephanie Jacobs; Dillon Timothy Wademan; Zara Kavalieratos; Mfundo Mlomzale; Arlene J Marthinus; Lucia N Jola (BMJ Open)
Introduction Adolescents’ experiences (10–19 years-old) with tuberculosis (TB) remain poorly understood. Descriptions of adolescent TB experiences, particularly how they interact with the health system, are scarce. We aimed to understand adolescents’ experiences of TB health services in the Western Cape, South Africa. We focused on how TB services were aided or hindered through interactions with healthcare providers and health system processes.Methods Teen TB, an observational study in Cape Town, enrolled 50 newly diagnosed adolescents with multidrug-resistant and drug-susceptible TB. A subset of 20 was selected for serial qualitative data collection, with 19 completing all tasks between December 2020 and September 2021. 52 interviews were conducted and thematically analysed using a case descriptive process for experiences across the TB care cascade.Findings Adolescents criticised the difficulties and delays they encountered in obtaining an accurate TB diagnosis. Initial misdiagnoses and delayed TB diagnoses were reported, despite seeking help from multiple healthcare providers at different facilities. Adolescents questioned whether the financial, social and emotional costs of TB care outweighed the costs of delaying treatment initiation and adherence. Adolescents reported that the treatment regimen, adherence support processes and interactions with the health system posed significant challenges to maintaining adherence. Encouragingly, however, most adolescents reported being well treated and cared for by health workers.Conclusion Our study shows that adolescents experience challenges throughout their TB treatment journeys. More adolescent-focused research is needed to tailor treatment and healthcare processes to their needs.